Interactive framework for dynamic modelling and active vibration control of flexible structures - Mat Darus, Intan Zaurah; Mohd. Hashim, Siti Zaiton; Tokhi, M. O. (Faculty of Mechanical Engineering, 2008)
This paper presents the implementation of an interactive learning environment for dynamic simulation and active vibration control of flexible structures. The study attempts to facilitate the learning process of the subject area through the development of an interactive environment that can help users to simulate and visualise the behaviour of flexible structures with given physical characteristics, and to test and validate controller designs. Furthermore, the environment allows users to execute such processes repeatedly in a friendly and easy manner. Simulation algorithms based on finite difference scheme in characterizing the dynamic behaviour of flexible structures with different boundary conditions are incorporated. Controller-design strategies, parametric as well as nonparametric, are integrated within this framework. The design and implementation of the interactive learning system incorporating the simulation algorithms, modelling and control strategies, are developed using MATLAB. The environment allows the user to specify the boundary conditions and physical properties of the structure including the dimensions and material type, and provides the response of the structure to user-specified disturbances in the time and frequency domains. The result of the simulation is further utilized in the modelling and control of the specified flexible structure. The environment, thus developed, forms a useful interactive and user-friendly learning and education facility.